ANALYSIS OF FACTORS AFFECTING THE VOLUME OF IMPORTS IN THE REPUBLIC OF UZBEKISTAN - Ro’ziyeva Dilobar Isomjonovna; Toshniyozov Sardor Nuriddinovich; Usmonov Navruzbek Erkin ugli (American Journals, 2025)
This article conducts an empirical analysis of the main factors affecting Uzbekistan's import volume for the period 2013-2024, including GDP and exchange rate. According to the results obtained using the OLS regression method, it was found that GDP has a positive and statistically significant effect on import volume. The exchange rate, on the other hand, did not have a significant effect on imports during this period. The results of the study are important for improving the country's foreign trade policy.
Keywords: Foreign Direct Investment (FDI), imports, Gross Domestic Product (GDP), exchange rate, OLS, regression analysis, Uzbekistan economy, Macroeconomic indicators.